Public goods, transferable utility and divorce laws - Pierre-André Chiappori; Murat Iyigun; Yoram Weiss (Institute for the Study of Labor (IZA), 2007)
We reconsider the well known Becker-Coase (BC) argument, according to which changes in divorce laws should not affect divorce rates, in the context of households which consume public goods in addition to private goods. For this result to hold, utility must be transferable both within marriage and upon divorce, and the marginal rate of substitution between public and private consumption needs to be invariant in marital status. We develop a model in which couples consume public goods and show that if divorce alters the way some goods are consumed (either because some goods that are public in marriage become private in divorce or because divorce affects the marginal rate of substitution between public and private goods), then the Becker-Coase theorem holds only under strict quasi-linearity. We conclude that, in general, divorce laws will influence the divorce rate, although the impact of a change in divorce laws can go in either direction
urn:nbn:de:101:1-20080416168
Keywords: 330; Ehe; Eherecht; Familienökonomik; Öffentliches Gut; Coase-Theorem; Nutzen; Theorie